Alleviation of Neuropathic Pain by Regulating T-Type Calcium Channels in Rat Anterior Cingulate Cortex - Shen, Feng-Yan; Chen, Zhi-Yu; Zhong, Wei; Ma, Li-Qing; Chen, Chong; Yang, Zhou-Jing; Xie, Wei-Lin; Wang, Ying-Wei (Molecular pain, 2015)
Background It has been demonstrated that administration of T-type calcium channel (TCC) inhibitors could relieve the neuropathic pain by intraperitoneally or intrathecally. TCCs are not only expressed in dorsal root ganglia or dorsal horn, but also in some of the pain associated brain regions. In the present study, we sought to investigate whether modulating TCCs in the anterior cingulate cortex (ACC) could alleviate the neuropathic pain. Results (1) Cav3.2 was up regulated in rat ACC after chronic constriction injury (CCI). (2) T-type calcium current intensity was increased in CCI animal model. (3) TCC inhibitor reduced miniature excitatory postsynaptic currents frequency of ACC neurons in CCI animal model. (4) TCC inhibitor suppressed the firing rate of ACC neurons in CCI animal model. (5) Both mechanical and thermal allodynia were partially relieved by ACC microinjection with TCC inhibitor. Conclusions TCCs in the ACC may be contributing to the maintenance of neuropathic pain, and the neuropathic pain can be alleviated by inhibiting the neuronal activity of ACC through modulating the TCCs.